Aortic size predicts aortic dissection in Turner syndrome - A 25-year prospective cohort study. (15th February 2023) - Thunström, Sofia; Thunström, Erik; Naessén, Sabine; Berntorp, Kerstin; Laczna Kitlinski, Margareta; Ekman, Bertil; Wahlberg, Jeanette; Bergström, Ingrid; Bech-Hanssen, Odd; Krantz, Emily; Laine, Christine M.; Bryman, Inger; et al.
Abstract: Background: Women with Turner syndrome (TS) have an increased risk of aortic dissection. The current recommended cutoff to prevent aortic dissection in TS is an aortic size index (ASI) of ≥2.5 cm/m 2 . This study estimated which aortic size had the best predictive value for the risk of aortic dissection, and whether adjusting for body size improved risk prediction. Methods: A prospective, observational study in Sweden, of women with TS, n  = 400, all evaluated with echocardiography of the aorta and data on medical history for up to 25 years. Receiver operating characteristic (ROC) curves, sensitivity and specificity were calculated for the absolute ascending aortic diameter (AAD), ascending ASI and TS specific z-score. Results: There were 12 patients (3%) with aortic dissection. ROC curves demonstrated that absolute AAD and TS specific z-score were superior to ascending ASI in predicting aortic dissection. The best cutoff for absolute AAD was 3.3 cm and 2.12 for the TS specific z-score, respectively, with a sensitivity of 92% for both. The ascending ASI cutoff of 2.5 cm/m 2 had a sensitivity of 17% only. Subgroup analyses in women with an aortic diameter ≥ 3.3 cm could not demonstrate any association between karyotype, aortic coarctation, bicuspid aortic valve, BMI, antihypertensive medication, previous growth hormone therapy or ongoing estrogen replacement treatment and aortic dissection. All models failed to predict a dissection in a pregnant woman. Conclusions: In Turner syndrome, absolute AAD and TS-specific z-score were more reliable predictors for aortic dissection than ASI. Care should be taken before and during pregnancy. Highlights: Aortic dissection in Turner syndrome is related to the size of the ascending aorta. The current strategies for preventing aortic dissection are insufficient. Aortic diameter cutoff of 3.3 cm is more reliable than the ASI cutoff of 2.5 cm/m 2 . The risk of aortic dissection is low for absolute aortic diameter < 3.3 cm.